Democratic accountability in Latin America - Mainwaring, Scott 1954-; Welna, Christopher (Oxford studies in democratization., 2003)
This volume on democratic accountability addresses one of the burning issues on the agenda of policy makers and citizens in contemporary Latin America: how democratic leaders in Latin America can improve accountability while simultaneously promoting governmental effectiveness.